2014
DOI: 10.5152/balkanmedj.2014.9418
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase Non-receptor 22 Gene C1858T Polymorphism in Patients with Coexistent Type 2 Diabetes and Hashimoto’s Thyroiditis

Abstract: Autoimmune thyroid diseases and diabetes mellitus exist together more often in comparison to other diseases. The existence ratio increases with age and affects autoimmune diabetics and females the most (1), while thyroid disorders are observed in about 10-15% of patients with diabetes mellitus and 6% of non-diabetics (2). Hashimoto's thyroiditis (HT), also known as chronic lymphocytic thyroiditis or chronic autoimmune thyroiditis (3), is the most common autoimmune thyroid disease, affecting up to 10% of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“… 72 74 Several studies have also shown that the SNP C1858T (rs2476601), that leads to the substitution of a tryptophan at position 620 of LYP for an arginine (R620W), is linked with both T1DM and AITD. 46 , 73 78 However, some contradictory results show that this SNP in PTPN22 is associated with AITD but not with T1DM. 79 Another report indicated that an SNP (rs2476601) in PTPN22 is not associated with AITD.…”
Section: Genetics and Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“… 72 74 Several studies have also shown that the SNP C1858T (rs2476601), that leads to the substitution of a tryptophan at position 620 of LYP for an arginine (R620W), is linked with both T1DM and AITD. 46 , 73 78 However, some contradictory results show that this SNP in PTPN22 is associated with AITD but not with T1DM. 79 Another report indicated that an SNP (rs2476601) in PTPN22 is not associated with AITD.…”
Section: Genetics and Autoimmunitymentioning
confidence: 99%
“…74 Bottini et al (2004);75 Velaga et al (2004);76 Bulut et al (2014);77 Smyth et al (2004);78 Lee et al (2011);79 Alkhateeb et al (2013);80 Liu et al (2015);81 Ikegami et al (2006); 82 El Fotoh et al (2019); 83 Giza et al (2013); 84 Wasniewska et al (2012); 85 Prezioso et al (2017); 86 Burn et al (2011); 87 Blasetti et al (Ban et al (2007); 94 Inoue et al (2010); 95 Villano et al (2009); 96 Li et al (2015); 97 Bossowski et al(2013); 98 Nakano et al (2007); 99 Korn et al (2009); 100 Li et al (2016); 101 Bjornvold et al (2006); 102 Rubio-Cabezas et al (2009); 103 Zavattari et al (2004); 104 Nakanishi and Shima (2007); 105 Brusko et al (2007); 106 Tritt et al (2008); 107 Brode et al (2006); 108 Tian et al (2009); 109 Jaeckel et al (2005); 110 Peng et al (2004); 111 Wu et al (2012); 112 Zheng et al (2009); 113 Johnson et al (2013) 114 Golden et al (2005); 43 Villano et al (2009); 96 Chen et al (2013); 121 Pastuszak-Lewandoska et al (2012); 122 Douroudis et al (2009); 123 Bednarczuk et al (2003); 124 Hou et al (2015); 125 Vaidya et al (1999); 126 Kavvoura et al (2007); 127 Lee et al (2000); 128 Ikegami et al (2006); 129 Mochizuki et al (2003); 130 Howson et al (2007); 131 Tang et al (2012); 132 Takara et al (2000); 133 Mayans et al (2007); 134 Balic et al (2009); 135 Ban et al (2001); 136 Celmeli et al (2013);137 Chen and Li (2019);138 Wang et al (2017); 139 Kavvoura et al (2005); 140 Liu et al (2013); 141 Dong et al (2014); 142 Fathima et al (2019); 143 Bicek et al (2009); 144 Einarsdottir et al (2003);146 Ban and Tomer (2003);147 Aversa et al148 (2019); Orban et al (2011); 149 Orban et al (2014)150 Abatacept AIRE, autoimmune regulator; AITD, thyroid autoimmune disease; CTLA-4, cytotoxic T lymphocyte-associated antigen-4; FOXP3, forkhead box protein P3; HLA, human leukocyte antigen; LYP, lymphoid protein tyrosine phosphatase; T1DM, type 1 diabetes mellitus.…”
mentioning
confidence: 99%
“…The polymorphism of C1858T was identified by restriction fragment length polymorphism (RFLP) as described by Bulut et al. [ 21 ]. The PCR product was cut by RsaI enzyme (New England Biolabs, Ipswich, MA) at 37 °C for 4 h and resulted in two fragments, 176 bp and 42 bp that indicated the homozygous CC (wild type), whereas the heterozygous CT had three fragments at 218, 176 and 42 bp (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Выявлены гены, позволяющие объяснить связь между СД 2-го типа и аутоиммунными заболеваниями щитовидной железы. В настоящее время идентифицировано по меньшей мере четыре общих гена, включая HLA [16], CTLA-4 [17], PTPN22 [18] и FOXP3 [19]. У пациентов с диабетом ночной ТТГпик «затуплен» и отмечено, что характерное «низкое состояние Т3» может быть обусловлено замедлением превращения Т4 в Т3 в периферических тканях, которое нормализуется с улучшением показателей гликемического контроля.…”
Section: факторы риска формирования сосудистых и нейропатических осло...unclassified